2021
DOI: 10.1080/07380577.2021.1926046
|View full text |Cite
|
Sign up to set email alerts
|

Social Prescribing Nomenclature, Occupational Therapy and the Theory of Institutional Work: Creating, Maintaining and Disrupting Medical Dominance

Abstract: Social prescribing is a process of helping people to access non-medical activities and services which address health and wellbeing needs. The process is frequently (although not exclusively) initiated by primary health care professionals and often involves prescribing activities or initiatives provided by community and voluntary organizations. To occupational therapy, the links between activity, social-connectedness and health are clearly not new, although there are emerging international examples of social pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Consistent with previous research,75–77 two studies38 41 in the current review reported reductions in primary healthcare use (consultation rates and medication prescribed) However, these findings should be interpreted with caution. Consistent with previous reviews of social prescribing interventions,4 8 9 75 the majority (15 out of 17) of the included studies were uncontrolled before-and-after studies (with a range of methodological shortcomings). Attrition rates were generally high (mean of 38%) and there was substantial variability in outcome measures.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Consistent with previous research,75–77 two studies38 41 in the current review reported reductions in primary healthcare use (consultation rates and medication prescribed) However, these findings should be interpreted with caution. Consistent with previous reviews of social prescribing interventions,4 8 9 75 the majority (15 out of 17) of the included studies were uncontrolled before-and-after studies (with a range of methodological shortcomings). Attrition rates were generally high (mean of 38%) and there was substantial variability in outcome measures.…”
Section: Discussionmentioning
confidence: 77%
“…This has been supported by purposive action, particularly influenced by the language of prescribing in primary care, to enhance the implementation of social prescribing in primary care. 9 Approximately one in six adults in the UK are living with mental health conditions 10 and social prescribing has the potential to improve outcomes for this population. Mental health has a devasting impact on individuals, their families and society, with depression and anxiety disorders affecting 16% of the UK population at any one time.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…There is an association between social prescription (HA recommendation) and occupational therapy, as this discipline has a long history of recommending activities to improve the health and well-being of individuals, groups, and communities [ 14 ]. Therefore, in this paper, special emphasis is placed on occupations as understood by occupational therapy.…”
Section: Introductionmentioning
confidence: 99%